2014
DOI: 10.2217/pgs.14.69
|View full text |Cite
|
Sign up to set email alerts
|

HLA-B*13:01 Is Associated with Salazosulfapyridine-Induced Drug Rash with Eosinophilia and Systemic Symptoms in Chinese Han Population

Abstract: These findings show for the first time that in the Chinese Han population, HLA-B*13:01 is associated with SASP-induced DRESS. HLA-B*13:01 might serve as a potential genetic marker for reducing the prevalence of SASP-induced DRESS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(17 citation statements)
references
References 43 publications
1
16
0
Order By: Relevance
“…Bolded text: Data analysis result was presented statistical significance (p-value < 0.05). (Cao et al, 2001) Caucasians (n = 265) (Cao et al, 2001) Hispanics (n = 234) North American (n = 187) (Cao et al, 2001) Asians (n = 358) (Cao et al, 2001) Carbamazepine HLA-B*15:02 SJS/TEN 7.66 0.20 0.00 0.00 0.00 4.87 (Nahoko and Yoshiro, 2013;Sukasem et al, 2014;Su et al, 2016 (Chantarangsu et al, 2009;Sukasem et al, 2014;Lauren et al, 2014) (Continued) (Cao et al, 2001) Caucasians (n = 265) (Cao et al, 2001) Hispanics (n = 234) North American (n = 187) (Cao et al, 2001) Asians (n = 358) (Cao et al, 2001) Co-trimoxazole HLA-B*38:01 SJS/TEN 0.00 0.40 2.45 1.71 1.07 0.42 (Lonjou et al, 2008;White et al, (Zhang et al, 2013;White et al, 2014;Tempark et al, 2017) Salazosulfa-Pyridine HLA-B*13:01 DRESS 5.96 0.00 0.00 0.00 0.00 3.34 (Yang et al, 2014) Methazolamide HLA-B*59:01 SJS/TEN 0.00 0.00 0.00 0.00 0.00 0.56 (Stephens et al, 2013;White et al, 2014;Yang et al, 2016 (Daly et al, 2009) HLA-A, human leukocyte antigen-A; HLA-B, human leukocyte antigen-B; HLA-C, human leukocyte antigen-C; AHS, abacavir hypersensitivity; CADRs, cutaneous adverse drug reactions; DRESS, drug reactions with eosinophilia and systemic symptoms; DILI, drug-induced liver injury; MPE, maculopapular exanthema; SCARs, severe cutaneous adverse reactions; SJS, Stevens-Johnson syndrome; TEN, toxic epidermal necrolysis. African Americans (n = 241) (Just et al, 1996) Caucasians (n = 265) (Begovich et al, 1992) Japanese (n = 371) (Sa...…”
Section: Population Structure Analysismentioning
confidence: 99%
“…Bolded text: Data analysis result was presented statistical significance (p-value < 0.05). (Cao et al, 2001) Caucasians (n = 265) (Cao et al, 2001) Hispanics (n = 234) North American (n = 187) (Cao et al, 2001) Asians (n = 358) (Cao et al, 2001) Carbamazepine HLA-B*15:02 SJS/TEN 7.66 0.20 0.00 0.00 0.00 4.87 (Nahoko and Yoshiro, 2013;Sukasem et al, 2014;Su et al, 2016 (Chantarangsu et al, 2009;Sukasem et al, 2014;Lauren et al, 2014) (Continued) (Cao et al, 2001) Caucasians (n = 265) (Cao et al, 2001) Hispanics (n = 234) North American (n = 187) (Cao et al, 2001) Asians (n = 358) (Cao et al, 2001) Co-trimoxazole HLA-B*38:01 SJS/TEN 0.00 0.40 2.45 1.71 1.07 0.42 (Lonjou et al, 2008;White et al, (Zhang et al, 2013;White et al, 2014;Tempark et al, 2017) Salazosulfa-Pyridine HLA-B*13:01 DRESS 5.96 0.00 0.00 0.00 0.00 3.34 (Yang et al, 2014) Methazolamide HLA-B*59:01 SJS/TEN 0.00 0.00 0.00 0.00 0.00 0.56 (Stephens et al, 2013;White et al, 2014;Yang et al, 2016 (Daly et al, 2009) HLA-A, human leukocyte antigen-A; HLA-B, human leukocyte antigen-B; HLA-C, human leukocyte antigen-C; AHS, abacavir hypersensitivity; CADRs, cutaneous adverse drug reactions; DRESS, drug reactions with eosinophilia and systemic symptoms; DILI, drug-induced liver injury; MPE, maculopapular exanthema; SCARs, severe cutaneous adverse reactions; SJS, Stevens-Johnson syndrome; TEN, toxic epidermal necrolysis. African Americans (n = 241) (Just et al, 1996) Caucasians (n = 265) (Begovich et al, 1992) Japanese (n = 371) (Sa...…”
Section: Population Structure Analysismentioning
confidence: 99%
“…We showed that the frequency of HLA-B*13:01 in the SASP-induced DRESS patients was significantly higher compared with general Chinese Han population from MHC database (OR ¼ 11.16; P ¼ 0.007), or with SASPtolerant patients (OR ¼ 13.00, P ¼ 0.004) (Yang et al, 2014).…”
Section: Hla-b*13:01 and Salazosulfapyridine-dressmentioning
confidence: 73%
“…The main pharmacogenetic associations described are with mutations on HLA‐B * 58: 01, HLA‐B * 31: 01, and HLA13: 01 with allopurinol, carbamazepine, and sulphonamides, respectively, in Chinese population, and other associations described are abacavir, HLA‐B * 5701 (OR > 50 and reproduced in more than one study); nevirapine, HLA‐Cw8‐B14 haplotype in Italian population; HLA‐Cw8 in Japanese population and HLA‐B * 3505 in Thai population; carbamazepine with promoter motilin gene (rs2894342) in Chinese population , , . However, there are no data in our population or in association with Sb5+.…”
Section: Discussionmentioning
confidence: 91%